Toothpaste Prevents Debonded Brackets on Erosive Enamel - Érico Luiz Damasceno Barros; Shelon Cristina Souza Pinto; Alvaro Henrique Borges; Mateus Rodrigues Tonetto; Roger Phillip Ellwood; Ian Pretty; Matheus Coelho Bandéca (The Scientific World Journal)
This study evaluated the effect of high fluoride dentifrice on the bond strength of brackets after erosive challenge. Eighty-four enamel specimens were divided into seven groups (n=12): WN (distilled water/no acid challenge), W3C (distilled water/3 cycles of acid challenge), and W6C (distilled water/6 cycles of acid challenge) were not submitted to dentifrice treatment. Groups RF3C (regular fluoride dentifrice/3 cycles of acid challenge) and RF6C (regular fluoride dentifrice/6 cycles of acid challenge) were treated with dentifrices containing 1450 μg F−/g and HF3C (high fluoride dentifrice/3 cycles of acid challenge) and HF6C (high fluoride dentifrice/6 cycles of acid challenge) were with 5000 μg F−/g. Acid challenges were performed for seven days. After bond strength test, there was no significant difference among groups submitted to 3 cycles of acid challenge (P>0.05). Statistically significant difference was found between the regular and high fluoride dentifrices after 6 cycles of acid challenge (<0.05). Similar areas of adhesive remaining were found among control groups and among groups W6C, RF3C, RF6C, HF3C, and HF6C. The high fluoride dentifrice was able to prevent the reduction of bond strength values of brackets submitted to acid challenge. Clinical relevance: the high fluoride toothpaste prevents debonded brackets on erosive enamel.